Atom-Economical Cross-Coupling of Internal and Terminal Alkynes to Access 1,3-Enynes - Liu, Mingyu (J Am Chem Soc, 2021)
Selective carbon–carbon (C–C) bond formation in chemical synthesis generally requires pre-functionalized building blocks. However, the requisite pre-functionalization steps undermine the efficiency of multi-step synthetic sequences, which is particularly problematic in large-scale applications, such as in the commercial production of pharmaceuticals. Herein, we describe a selective and catalytic method for synthesizing 1,3-enynes without pre-functionalized building blocks. This method is facilitated by a tailored P,N-ligand that enables regioselective dimerization and suppresses secondary E/Z-isomerization of the product. The transformation enables several classes of unactivated internal acceptor alkynes to be coupled with terminal donor alkynes to deliver 1,3-enynes in a highly regio- and stereoselective manner. The scope of compatible acceptor alkynes includes propargyl alcohols, (homo)propargyl amine derivatives, and (homo)propargyl carboxamides. The reaction is scalable and can operate effectively with as low as 0.5 mol% catalyst loading. The products are versatile intermediates that can participate in various downstream transformations. We also present preliminary mechanistic experiments that are consistent with a redox-neutral Pd(II) catalytic cycle.